The Influence of Supervision and Human Resource Development on Employee Performance at the Regional Secretariat Office, Goods/Services Procurement Division, Maros Regency - Tajuddin; Syahrir (www.amertainstitute.com, 2024)
This study aims to determine the effect of Supervision and Human Resource Development on employee performance at the Regional Secretariat Office for Goods/Services Procurement Section of Maros Regency. The type of research used is quantitative research. The data used in this study are primary and secondary data in the form of data available at the Regional Secretariat Office for Goods/Services Procurement Section. The population in this study consists of all employees in the goods/services procurement section at the Regional Secretariat Office of Maros Regency, totaling 40 people. The analysis method used in this study is multiple linear regression, as presented in the research results. The research results show that Supervision (X1) and Human Resource Development (X2) on Employee Performance (Y) at the Regional Secretariat Office for Goods/Services Procurement in Maros Regency have a positive and significant effect. Based on the t-test results, for the supervision variable on performance, the supervision variable has a t-value of (6.804) > t-table (1.692) and a significance value < 0.05, which is 0.000. The t-value is greater than the t-table, indicating a positive effect, and the significance value is less than 0.05, indicating significance. For the Human Resource Development variable on performance, the Human Resource Development variable has a t-value of (3.774) > t-table (1.692) and a significance value < 0.05, which is 0.001. The t-value is greater than the t-table, indicating a positive effect, and the significance value is less than 0.05, indicating significance. Which means that simultaneously, the influence of Supervision and Human Resource Development has a positive and significant effect on the Performance of the Regional Secretariat Office for the Goods/Services Procurement Section of Maros Regency.